2008
DOI: 10.1111/j.1582-4934.2008.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional effects of caloxin 1c2, a novel engineered selective inhibitor of plasma membrane Ca2+‐pump isoform 4, on coronary artery

Abstract: Coronary artery smooth muscle expresses the plasma membrane Ca2+ pump (PMCA) isoforms PMCA4 and PMCA1. We previously reported the peptide inhibitor caloxin 1b1 that was obtained by using extracellular domain 1 of PMCA4 as the target (Am J Physiol Cell.290 [2006] C1341). To engineer inhibitors with greater affinity and isoform selectivity, we have now created a phage display library of caloxin 1b1-like peptides. We screened this library by affinity chromatography with PMCA from erythrocyte ghosts that contain m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 64 publications
2
27
0
Order By: Relevance
“…This method was used for caloxin 1b1 [92]. The hypothesis was that altering one, two, or three residues in caloxin 1b1 may improve its affinity and isoform selectivity, and yet maintain its ability to inhibit PMCA.…”
Section: Screening Phage Display Librariesmentioning
confidence: 99%
“…This method was used for caloxin 1b1 [92]. The hypothesis was that altering one, two, or three residues in caloxin 1b1 may improve its affinity and isoform selectivity, and yet maintain its ability to inhibit PMCA.…”
Section: Screening Phage Display Librariesmentioning
confidence: 99%
“…In vascular smooth muscle, ATP2B1 and ATP2B4 have been also shown to be expressed. 18 However, there were few reports evaluating the role of ATP2B1 in VSMCs. Thus, we decided to knock out the ATP2B1 gene of VSMCs to clarify the function of the ATP2B1 gene in hypertension theoretically in humans.…”
Section: Implication Of Atp2b1 In Blood Pressure Control and Functionmentioning
confidence: 99%
“…In contrast to studies on transgenic mice it has been shown that the PMCA inhibitor caloxin 1c2, which has 10x greater affinity for PMCA4 when compared to PMCA1, 2 or 3, increased coronary artery smooth muscle contractility [86]. Studies in cultured vascular smooth muscle cells have shown that inhibition of PMCA4 with another PMCA4 inhibitor, caloxin 1b1, results in a rise in [Ca 2+ ] i .…”
Section: Pmca4 and Vascular Contractilitymentioning
confidence: 87%